MOF-5 and preparation and application thereof, polymer self-lubricating composite material and preparation and application thereof

By adding capping agent and weak base during the preparation of MOF-5 and using ultrasonic treatment, the micromorphology and particle size of MOF-5 are suitable, which solves the problem of high volume wear in lubricating materials and improves the tribological properties of polymer self-lubricating composite materials.

CN119775584AActive Publication Date: 2025-04-08LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510000793.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

When used in lubricating materials, MOF-5 has high tribological properties, especially volume wear, and it is difficult to meet actual needs.

Method used

By adding a capping agent and a weak base during the preparation of MOF-5, the ultrasonic treatment method was used to make the micromorphic morphology of MOF-5 layered, with a particle size of 1 to 5 μm, and the crystal surface was specifically exposed, thereby improving its performance in polymer self-lubricating composite materials.

Benefits of technology

It effectively reduces the volume wear of polymer self-lubricating composite materials, improves its tribological properties, and makes it perform better in applications such as sliding bearings, gas compressors or automotive brake systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775584A_ABST
    Figure CN119775584A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional materials, and provides MOF-5 and preparation and application thereof, and a polymer self-lubricating composite material and preparation and application thereof. The preparation method comprises the following steps: mixing zinc salt, terephthalic acid, an end-capping reagent (polyvinyl pyrrolidone or polyvinyl alcohol), a weak base (triethylamine or sodium acetate) and a solvent, and carrying out ultrasonic treatment. The end-capping reagent and the weak base are added, so that the microstructure of the MOF-5 is lamellar, and the specificity of the crystal face is exposed, and when the MOF-5 is used as a functional filler to be applied to the self-lubricating polymer, the tribological performance can be improved. The MOF-5 mainly provides a reinforcing effect similar to that of crushed carbon fibers, and in the frictional wear process of the polymer self-lubricating composite material and a metal pair, the MOF-5 mainly serves as a bearing phase to bear main loads and makes contact with the metal pair to form a uniform and continuous transfer film on the surface of the metal pair, so that the metal pair is protected against abrasion. The tribological property of the polymer self-lubricating composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to MOF-5 and preparation and application thereof, and polymer self-lubricating composite materials and preparation and application thereof. Background Art

[0002] As a new type of material with wide applications, MOFs are often used in gas storage and transportation, organic catalysis, drug delivery and release, etc. In addition, organic ligands endow MOFs with abundant active groups on their surfaces. With rich mesoporous structures, high thermal stability, excellent mechanical properties, and active surface groups, MOFs are often used as functional fillers in the field of polymer composites. They can enhance the mechanical properties of composite materials and improve the flame retardant properties of materials.

[0003] At the same time, as a classic MOFs material, MOF-5 has excellent specific surface area, adsorption, abundant active sites and stable framework structure, and can be used as a functional filler. In the existing technology, MOF-5 is used in dye wastewater treatment, carbon dioxide adsorption, and lithium-sulfur batteries, with relatively good results; however, when MOF-5 is used in lubricating materials, the tribological properties, especially the volume wear, are high. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a MOF-5 and its preparation and application, a polymer self-lubricating composite material and its preparation and application. The MOF-5 provided by the present invention is added as a functional material to a self-lubricating polymer, which can reduce the volume wear of the obtained polymer self-lubricating composite material, thereby improving the tribological properties of the polymer self-lubricating composite material.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing MOF-5, comprising the following steps:

[0007] The zinc salt, terephthalic acid, a capping agent, a weak base and a solvent are mixed and subjected to ultrasonic treatment to obtain the MOF-5;

[0008] The end-capping agent includes polyvinyl pyrrolidone or polyvinyl alcohol;

[0009] The weak base includes triethylamine or sodium acetate.

[0010] Preferably, the zinc salt comprises zinc nitrate and / or zinc acetate, and the solvent comprises N-methylpyrrolidone.

[0011] Preferably, the mass ratio of the zinc salt to terephthalic acid is 5-20:2-6;

[0012] The mass ratio of terephthalic acid to the end-capping agent is 2-6:0-6, and the mass of the end-capping agent is not 0;

[0013] The mass ratio of terephthalic acid to weak base is 2-6:0-5, and the mass of the weak base is not 0;

[0014] The mass ratio of the zinc salt to the solvent is 5 to 20:100.

[0015] Preferably, the ultrasonic treatment is performed at a power of 500 to 800 W and for a time of 20 to 60 min.

[0016] The present invention also provides MOF-5 prepared by the preparation method described in the above technical scheme.

[0017] The present invention also provides the use of the MOF-5 described in the above technical solution in a polymer self-lubricating composite material.

[0018] The present invention also provides a polymer self-lubricating composite material, comprising MOF-5 and polyetheretherketone, wherein the MOF-5 is the MOF-5 described in the above technical solution.

[0019] Preferably, the mass ratio of polyetheretherketone to MOF-5 is 33.6:0.3-3.5.

[0020] The present invention also provides a method for preparing the polymer self-lubricating composite material described in the above technical solution, comprising the following steps:

[0021] The polyetheretherketone and MOF-5 are mixed and hot-pressed to obtain the polymer self-lubricating composite material.

[0022] The present invention also provides the use of the polymer self-lubricating composite material described in the above technical solution or the polymer self-lubricating composite material prepared by the preparation method described in the above technical solution in sliding bearings, gas compressors or vehicle braking systems.

[0023] The invention provides a method for preparing MOF-5.

[0024] The preparation method provided by the present invention adds a capping agent and a weak base, so that the microscopic morphology of MOF-5 is lamellar, the particle size is 1 to 5 μm, and the crystal surface is specifically exposed, so that when it is used as a functional filler in a self-lubricating polymer, the volume wear of the obtained polymer self-lubricating composite material can be reduced, and the tribological properties of the polymer self-lubricating composite material are improved. At the same time, the ultrasonic treatment of the present invention can make the synthesis amount relatively large, which is suitable for industrial production.

[0025] The present invention also provides a polymer self-lubricating composite material. The polymer self-lubricating composite material of the present invention is compounded with polyetheretherketone and the MOF-5 described in the above technical solution. MOF-5 mainly provides a reinforcement effect similar to crushed carbon fiber. In the friction and wear process between the polymer self-lubricating composite material and the metal pair, MOF-5 mainly acts as a bearing phase, bears the main load, and contacts with the metal pair to form a uniform and continuous transfer film on the surface of the metal pair, thereby reducing the volume wear of the metal pair on the polymer self-lubricating composite material and improving the tribological properties of the polymer self-lubricating composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the MOF-5 nanoparticles obtained in Example 1;

[0027] Figure 2 The XRD spectrum of MOF-5 nanoparticles obtained in Example 1;

[0028] Figure 3 is an evolution curve of the friction coefficient of the polymer self-lubricating composite material obtained in Example 1 over time;

[0029] Figure 4 This is a scanning electron microscope image of the worn surface obtained after the friction performance test of the polymer self-lubricating composite material obtained in Example 1;

[0030] Figure 5 This is a scanning electron microscope image of the transfer film on the metal dual surface after the friction performance test of the polymer self-lubricating composite material obtained in Example 1. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing MOF-5, comprising the following steps:

[0032] The zinc salt, terephthalic acid, a capping agent, a weak base and a solvent are mixed and subjected to ultrasonic treatment to obtain the MOF-5;

[0033] The end-capping agent includes polyvinyl pyrrolidone or polyvinyl alcohol;

[0034] The weak base includes triethylamine or sodium acetate.

[0035] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0036] In the present invention, the zinc salt preferably includes zinc nitrate and / or zinc acetate, and more preferably zinc nitrate. In the present invention, the zinc nitrate is preferably zinc nitrate hexahydrate. In the present invention, the zinc acetate is preferably zinc acetate dihydrate.

[0037] In the present invention, the terephthalic acid is used as the organic ligand.

[0038] In the present invention, the end-capping agent includes polyvinyl pyrrolidone (PVP) or polyvinyl alcohol (PVA), preferably polyvinyl pyrrolidone.

[0039] In the present invention, the weak base includes triethylamine (TEA) or sodium acetate (NaAc), preferably triethylamine.

[0040] In the present invention, the solvent preferably includes N-methylpyrrolidone (NMP).

[0041] In the present invention, the mass ratio of the zinc salt to terephthalic acid is preferably 5-20:2-6, and specifically preferably 13.9:3.34 or 10.2:3.34.

[0042] In the present invention, the mass ratio of terephthalic acid to the end-capping agent is preferably 2-6:0-6, and the mass of the end-capping agent is not 0, more preferably 2-6:0.1-6, and specifically preferably 3.34:3.36.

[0043] In the present invention, the mass ratio of terephthalic acid to weak base is preferably 2-6:0-5, and the mass of the weak base is not 0, more preferably 2-6:0.1-5, and specifically preferably 3.34:1.47.

[0044] In the present invention, the mass ratio of the zinc salt to the solvent is preferably 5 to 20:100, and specifically preferably 13.9:100 or 10.2:100.

[0045] In the present invention, the power of the ultrasonic treatment is preferably 500-800 W, specifically preferably 500 W, 600 W, 650 W, 700 W or 800 W; the time is preferably 20-60 min, specifically preferably 20 min, 30 min, 40 min, 50 min or 60 min.

[0046] After the ultrasonic treatment is completed, the present invention preferably further comprises solid-liquid separation of the obtained feed liquid, and the obtained solid is washed and dried in sequence to obtain the MOF-5. In the present invention, the solid-liquid separation method is preferably centrifugation. In the present invention, the washing reagent is preferably ethanol, the washing method is preferably centrifugal washing, and the number of washings is preferably 3 times. In the present invention, the drying temperature is preferably 100-140°C, more preferably 120°C, and the time is preferably 8-16h, specifically preferably 8h, 10h, 12h or 16h.

[0047] The present invention adds a capping agent and a weak base to make the microscopic morphology of MOF-5 lamellar, the particle size is 1 to 5 μm, and the crystal surface is specifically exposed, so that when it is used as a functional filler in a self-lubricating polymer, the volume wear of the polymer self-lubricating composite material can be reduced and the tribological properties of the polymer self-lubricating composite material can be improved. At the same time, the ultrasonic treatment of the present invention can make the synthesis amount relatively large, which is suitable for industrial production.

[0048] The present invention also provides MOF-5 prepared by the preparation method described in the above technical scheme.

[0049] In the present invention, the MOF-5 is a metal organic framework material with a Zn ion cluster as a metal center and terephthalic acid as an organic ligand.

[0050] In the present invention, the morphology of the MOF-5 is preferably lamellar. In the present invention, the particle size of the MOF-5 is preferably 1 to 5 μm.

[0051] The present invention also provides the use of the MOF-5 described in the above technical solution in a polymer self-lubricating composite material.

[0052] The present invention also provides a polymer self-lubricating composite material, comprising MOF-5 and polyetheretherketone, wherein the MOF-5 is the MOF-5 described in the above technical solution.

[0053] In a specific embodiment of the present invention, the polyetheretherketone is preferably a blocked polyetheretherketone, and further preferably a blocked polyetheretherketone (FD-PEEK) 770PF-200 provided by Zhongyan Co., Ltd.

[0054] In the present invention, the mass ratio of polyetheretherketone to MOF-5 is preferably 33.6:0.3-3.5, and specifically preferably 33.6:0.3, 33.6:0.7, 33.6:1.4, 33.6:2.8 or 33.6:3.5.

[0055] In the present invention, MOF-5 in the polymer self-lubricating composite material mainly provides a reinforcing effect similar to that of crushed carbon fibers. In the friction and wear process between the polymer self-lubricating composite material and the metal counterpart, MOF-5 mainly acts as a bearing phase, bears the main load, and contacts the metal counterpart to form a uniform and continuous transfer film on the surface of the metal counterpart. The formation of the transfer film can reduce the volume wear of the metal counterpart on the polymer self-lubricating composite material, thereby improving the tribological properties of the polymer self-lubricating composite material.

[0056] The present invention also provides a method for preparing the polymer self-lubricating composite material described in the above technical solution, comprising the following steps:

[0057] The polyetheretherketone and MOF-5 are mixed and hot-pressed to obtain the polymer self-lubricating composite material.

[0058] In the present invention, the polyetheretherketone is preferably used in the form of polyetheretherketone powder, and the particle size of the polyetheretherketone powder is preferably 200 mesh. In the present invention, the particle size of the MOF-5 is preferably 1 to 5 μm.

[0059] The polyetheretherketone and MOF-5 are preferably pretreated before use in the present invention. The pretreatment is preferably drying. The drying temperature is preferably 120° C. and the drying time is preferably 8 hours.

[0060] In the present invention, the mixing of polyetheretherketone and MOF-5 is preferably carried out in a high-speed disperser.

[0061] In the present invention, the temperature of the hot pressing is preferably 380-420°C, specifically preferably 380°C, 390°C, 400°C, 410°C or 420°C; the pressure is preferably 3-6MPa, specifically preferably 3MPa, 4MPa, 5MPa or 6MPa; the time is preferably 0.5-2h, specifically preferably 0.5h, 1h, 1.5h or 2h.

[0062] The present invention also provides the use of the polymer self-lubricating composite material described in the above technical solution or the polymer self-lubricating composite material prepared by the preparation method described in the above technical solution in sliding bearings, gas compressors or vehicle braking systems.

[0063] In the present invention, the polymer self-lubricating composite material is applied to a sliding bearing, and the polymer self-lubricating composite material is preferably made into a bearing retainer.

[0064] In the present invention, the polymer self-lubricating composite material is applied to a gas compressor, and the polymer self-lubricating composite material is preferably made into a sealing member.

[0065] In the present invention, the polymer self-lubricating composite material is applied to a vehicle braking system, and the polymer self-lubricating composite material is preferably made into a brake pad.

[0066] The MOF-5 and its preparation and application, the polymer self-lubricating composite material and its preparation and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0067] The polyetheretherketone used in the following examples is the blocked polyetheretherketone (FD-PEEK) 770PF-200 provided by Zhongyan Co., Ltd.

[0068] Example 1

[0069] 1. Synthesis of MOF-5

[0070] 13.9g zinc nitrate hexahydrate, 3.34 terephthalic acid, 3.36g polyvinylpyrrolidone (PVP), 1.47g triethylamine (TEA) were weighed in a 500mL glass beaker by an analytical balance and dissolved in 100g N-methylpyrrolidone (NMP). Subsequently, an ultrasonic generator was inserted, the power of the ultrasonic generator was adjusted to 650W, and ultrasonic treatment was performed for 30min; finally, the feed liquid was centrifuged to collect the solid, and ethanol was used as a washing reagent for the solid, and the solid was centrifuged and washed 3 times, and then dried in an oven at 120°C overnight to obtain MOF-5 nanoparticles with a particle size of 1 to 5μm.

[0071] 2. Preparation of polymer self-lubricating composites

[0072] First, the PEEK (200 mesh) and MOF-5 nanoparticles to be used were dried in an oven at 120°C for 8 hours, then 33.6g of PEEK and 1.4g of MOF-5 nanoparticles were weighed by an electronic balance, and the powders were mixed evenly by a high-speed disperser, and finally hot-pressed at 400°C for 1 hour under a controlled pressure of 4MPa to obtain a sheet-like polymer self-lubricating composite material. The sheet was cut into sample pins of 4×4×12mm for friction performance testing.

[0073] Example 2

[0074] 1. Synthesis of MOF-5

[0075] 13.9g zinc nitrate hexahydrate, 3.34 terephthalic acid, 3.36g polyvinylpyrrolidone (PVP), 1.47g triethylamine (TEA) were weighed in a 500mL glass beaker by an analytical balance and dissolved in 100g N-methylpyrrolidone (NMP). Subsequently, an ultrasonic generator was inserted, the power of the ultrasonic generator was adjusted to 650W, and ultrasonic treatment was performed for 30min; finally, the feed liquid was centrifuged to collect the solid, and ethanol was used as a washing reagent for the solid, and the solid was centrifuged and washed 3 times, and then dried in an oven at 120°C overnight to obtain MOF-5 nanoparticles with a particle size of 1 to 5μm.

[0076] 2. Preparation of polymer self-lubricating composites

[0077] First, the PEEK (200 mesh) and MOF-5 nanoparticles to be used were dried in an oven at 120°C for 8 hours, then 33.6g PEEK and 2.8g MOF-5 were weighed by an electronic balance, and the powders were mixed evenly by a high-speed disperser, and finally hot-pressed at 400°C for 1 hour under a controlled pressure of 4MPa to obtain a sheet-like polymer self-lubricating composite material. The sheet was cut into sample pins of 4×4×12mm for friction performance testing.

[0078] Example 3

[0079] 1. Synthesis of MOF-5

[0080] 13.9 g of zinc nitrate hexahydrate, 3.34 terephthalic acid, 3.36 g of polyvinyl pyrrolidone (PVP), and 1.47 g of triethylamine (TEA) were weighed in a 500 mL glass beaker using an analytical balance and dissolved in 100 g of N-methylpyrrolidone (NMP). Subsequently, an ultrasonic generator was inserted, the power of the ultrasonic generator was adjusted to 650 W, and ultrasonic treatment was performed for 30 min. Finally, the solid was collected by centrifugation of the feed liquid, and ethanol was used as a washing agent to centrifuge and wash the solid 3 times, and then dried in an oven at 120 ° C overnight to obtain MOF-5 nanoparticles with a particle size of 1 to 5 μm.

[0081] 2. Preparation of polymer self-lubricating composites

[0082] First, the PEEK (200 mesh) and MOF-5 nanoparticles to be used were dried in an oven at 120°C for 8 hours, then 33.6g PEEK and 0.7g MOF-5 were weighed by an electronic balance, and the powders were mixed evenly by a high-speed disperser, and finally hot-pressed at 400°C for 1 hour under a controlled pressure of 4MPa to obtain a sheet-like polymer self-lubricating composite material. The sheet was cut into sample pins of 4×4×12mm for friction performance testing.

[0083] Example 4

[0084] 1. Synthesis of MOF-5

[0085] 10.2g zinc acetate dihydrate, 3.34 terephthalic acid, 3.36g polyvinyl alcohol (PVA), 1.47g sodium acetate (NaAc) were weighed in a 500mL glass beaker by an analytical balance and dissolved in 100g N-methylpyrrolidone (NMP). Subsequently, an ultrasonic generator was inserted, the power of the ultrasonic generator was adjusted to 650W, and ultrasonic treatment was performed for 30min; finally, the feed liquid was centrifuged to collect the solid, and ethanol was used as a washing reagent for the solid, and the solid was centrifuged and washed 3 times, and then dried in an oven at 120°C overnight to obtain MOF-5 nanoparticles with a particle size of 1 to 5μm.

[0086] 2. Preparation of polymer self-lubricating composites

[0087] First, the PEEK (200 mesh) and MOF-5 nanoparticles to be used were dried in an oven at 120°C for 8 hours, then 33.6g of PEEK and 2.8g of MOF-5 were weighed by an electronic balance, and the powders were mixed evenly by a high-speed disperser, and finally a hot pressing process was performed, and the applied pressure was controlled to be 4MPa and hot pressed at 400°C for 1 hour to obtain a sheet-like polymer self-lubricating composite material. The sheet was cut into sample pins of 4×4×12mm for friction performance testing.

[0088] Comparative Example 1

[0089] 1. Synthesis of MOF-5

[0090] 13.9 g of zinc nitrate hexahydrate and 3.34 terephthalic acid were weighed in a 500 mL glass beaker by an analytical balance and dissolved in 100 g of N-methylpyrrolidone (NMP). Subsequently, an ultrasonic generator was inserted, and the power of the ultrasonic generator was adjusted to 650 W, and ultrasonic treatment was performed for 30 minutes; finally, the feed liquid was centrifuged to collect the solid, and ethanol was used as a washing reagent for the solid, and the solid was centrifuged and washed 3 times, and then dried in an oven at 120°C overnight to obtain MOF-5 nanoparticles.

[0091] 2. Preparation of polymer self-lubricating composites

[0092] First, the PEEK (200 mesh) and MOF-5 powder materials to be used were dried in an oven at 120°C for 8 hours, then 33.6g PEEK and 1.4g MOF-5 were weighed by an electronic balance, and the above powders were mixed evenly by a high-speed disperser, and finally hot pressed at 400°C for 1 hour under a controlled pressure of 4MPa to obtain a plate-like polymer self-lubricating composite material, which was recorded as a PEEK / MOF-5 composite material. The plate was cut into sample pins of 4×4×12mm for friction performance testing.

[0093] Comparative Example 2

[0094] 35g PEEK (200 mesh) was weighed by an electronic balance, and the powder was evenly mixed by a high-speed disperser, and finally hot pressed at 400°C for 1h under a controlled pressure of 4MPa to obtain a plate-like composite material. The plate was cut into sample pins of 4×4×12mm for friction performance testing.

[0095] The composite materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to friction performance tests. The parameters of the friction performance tests included: positive pressure of 4 MPa, linear speed of 1 m / s, test duration of 2 h, and metal pair material of Cr15 rolling bearing steel. The volume wear rate was calculated by Ws = (m1-m2) / ρFL, where m1 is the mass of the sample pin before the friction test, m2 is the mass of the sample pin after the friction test, ρ is the density of the sample pin, F is the positive load, and L is the total experimental mileage. The results are shown in Table 1.

[0096] Table 1 Friction performance results of the composite materials obtained in the examples and comparative examples

[0097] Steady-state friction coefficient <![CDATA[Volume wear rate (×10 -6 mm 3 / Nm)]]> Example 1 0.43 2.4 Example 2 0.45 4.6 Example 3 0.45 5.7 Example 4 0.48 5.5 Comparative Example 1 0.49 3.2 Comparative Example 2 0.38 7.8

[0098] It can be seen from Table 1 that the MOF-5 synthesized by end-capping agent and weak base induction can be used as a tribological performance enhancing filler to effectively improve the friction and wear resistance of the polymer self-lubricating composite material. The amount of MOF-5 added will affect the tribological properties of the polymer self-lubricating composite material. Among them, the polymer self-lubricating composite material in Example 1 has the best friction and wear performance.

[0099] Figure 1 This is a scanning electron microscope image of the MOF-5 nanoparticles obtained in Example 1. Figure 1 It can be seen that MOF-5 is mainly a flake structure with a particle size between 1 and 5 μm.

[0100] Figure 2 The XRD spectrum of MOF-5 nanoparticles obtained in Example 1 is shown in Figure 2 It can be seen that MOF-5 with crystal face-specific exposure was successfully synthesized.

[0101] Figure 3 The friction coefficient of the self-lubricating polymer composite material obtained in Example 1 changes with time. Figure 3 It can be seen that after a running-in period of 1500 s, the polymer self-lubricating composite material enters a steady state with a friction coefficient of 0.48.

[0102] Figure 4 This is a scanning electron microscope image of the wear surface obtained after the friction performance test of the polymer self-lubricating composite material obtained in Example 1. Figure 4 The MOF-5 particles embedded in the matrix can be clearly observed, indicating that MOF-5 plays a bearing role in the friction and wear process of the composite material. At the same time, the MOF-5 flakes are peeled off, which should be attributed to the peeling effect of the interface shear force on MOF-5.

[0103] Figure 5 This is a scanning electron microscope image of the transfer film on the metal dual surface after the friction performance test of the polymer self-lubricating composite material obtained in Example 1. Figure 5 It can be found that a smooth and continuous transfer film is formed on the metal dual surface. The formation of the transfer film should be attributed to the promotion effect of MOF-5. At the same time, the smooth transfer film is also conducive to the improvement of the anti-wear performance of the composite material.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing MOF-5, characterized in that: The following steps are involved: The zinc salt, terephthalic acid, a capping agent, a weak base and a solvent are mixed and subjected to ultrasonic treatment to obtain the MOF-5; The end-capping agent includes polyvinyl pyrrolidone or polyvinyl alcohol; The weak base includes triethylamine or sodium acetate.

2. The preparation method according to claim 1, characterized in that: The zinc salt includes zinc nitrate and / or zinc acetate, and the solvent includes N-methylpyrrolidone.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the zinc salt to terephthalic acid is 5-20:2-6; The mass ratio of terephthalic acid to the end-capping agent is 2-6:0-6, and the mass of the end-capping agent is not 0; The mass ratio of terephthalic acid to weak base is 2-6:0-5, and the mass of the weak base is not 0; The mass ratio of the zinc salt to the solvent is 5 to 20:

100.

4. The preparation method according to claim 1, characterized in that: The power of the ultrasonic treatment is 500-800W, and the time is 20-60min.

5. MOF-5 obtained by the preparation method according to any one of claims 1 to 4.

6. Use of the MOF-5 described in claim 5 in polymer self-lubricating composite materials.

7. A polymer self-lubricating composite material, characterized in that: It comprises MOF-5 and polyetheretherketone, and the MOF-5 is the MOF-5 described in claim 5.

8. The polymer self-lubricating composite material according to claim 7, characterized in that: The mass ratio of the polyetheretherketone to MOF-5 is 33.6:0.3-3.

5.

9. The method for preparing the polymer self-lubricating composite material according to any one of claims 7 to 8, characterized in that: The following steps are involved: The polyetheretherketone and MOF-5 are mixed and hot-pressed to obtain the polymer self-lubricating composite material.

10. Use of the polymer self-lubricating composite material according to any one of claims 7 to 8 or the polymer self-lubricating composite material prepared by the preparation method according to claim 9 in sliding bearings, gas compressors or vehicle brake systems.

Citation Information

Patent Citations

  • Method for preparing two-dimensional nanosheet nickel-based metal organic framework material

    CN113444259A

  • Self-lubricating fiber fabric and self-lubricating liner fabric composite material and preparation method thereof

    CN115807330A

  • Composite polymer self-lubricating shaft sleeve material, preparation method thereof and shaft sleeve

    CN118812996A

Cited By

  • MOFs (Metal-Organic Frameworks) reinforced polyether-ether-ketone composite material as well as preparation method and application thereof

    CN120346368A

  • Mofs reinforced polyether ether ketone composites, methods of making and using the same

    CN120346368B